Development of a latency model for HIV-1 subtype C and the impact of long terminal repeat element genetic variation on latency reversal - Shreyal Maikoo; Robert-Jan Palstra; Krista L. Dong; Tokameh Mahmoudi; Thumbi Ndung'u; Paradise Madlala (Journal of Virus Eradication)
Sub-Saharan Africa accounts for almost 70 % of people living with HIV (PLWH) worldwide, with the greatest numbers centred in South Africa where 98 % of infections are caused by subtype C (HIV-1C). However, HIV-1 subtype B (HIV-1B), prevalent in Europe and North America, has been the focus of most cure research and testing despite making up only 12 % of HIV-1 infections globally. Development of latency models for non-subtype B viruses is a necessary step to address this disproportionate focus. Furthermore, the impact of genetic variation between viral subtypes, specifically within the long terminal repeat (LTR) element of the viral transcriptional promoter on latency reversal, remains unclear. To address this scientific gap, we constructed a minimal genome retroviral vector expressing HIV-1C consensus transactivator of transcription protein (Tat) and green fluorescent protein (GFP) under the control of either HIV-1C consensus LTR (C731CC) or the transmitted/founder (T/F) LTRs derived from PLWH (CT/F731CC), produced corresponding LTR pseudotyped viruses using a vesicular stomatitis virus (VSV-G) pseudotyped Envelope vector and the pCMVΔR8.91 packaging vector containing HIV-1 accessory and rev genes. Viruses produced in this way were used to infect Jurkat E6 and primary CD4+ T cells in vitro. By enriching for latently infected cells, and treating them with different latency reversing agents, we developed an HIV-1C latency model that demonstrated that the HIV-1C consensus LTR has lower reactivation potential compared to its HIV-1B counterpart. Furthermore, HIV-1C T/F LTR pseudotyped proviral genetic variants exhibited a heterogenous reactivation response which was modulated by host cell (genetic) variation. Our data suggests that genetic variation both within and between HIV-1 subtypes influences latency reversal. Future studies should investigate the specific role of variation in host cellular environment on reactivation differences.